Analysis of health service quality and its association with patient satisfaction in hospital: A cross-sectional study - Danisyah Cahyo; Afif Kurniawan; Iswati Iswati; Firnanda Erindia (School of Health Sciences Al-Ma'arif, 2025)
Background: Patient satisfaction is a core indicator of healthcare performance and a major determinant of service utilization, trust, and loyalty. The quality of healthcare services is influenced by multiple dimensions, and the SERVQUAL (RATER) framework is widely used to assess patient perceptions of service quality. Evidence from Indonesian maternal and child hospitals remains limited, particularly regarding the role of tangible and interpersonal service attributes. Objective: This study aimed to analyze the association between health service quality based on RATER dimensions and patient satisfaction at RSIA IBI Surabaya. Methods: A quantitative analytic study with a cross-sectional design was conducted among 60 respondents selected using purposive sampling. Data were collected using a structured questionnaire with a four-point Likert scale and analyzed using Spearman Rank correlation to examine the relationship between each RATER dimension and satisfaction levels. Ethical principles were maintained through informed consent, anonymity, and voluntary participation. Results: Most respondents perceived the quality of healthcare services as high across the RATER dimensions, dominated by empathy (65.0%) and tangibles (60.0%). Patient satisfaction was also mostly high (83.3%). All dimensions demonstrated statistically significant correlations with satisfaction (p < 0.05), where tangibles (r = 0.615) and responsiveness (r = 0.592) were identified as the strongest predictors. Conclusion: Health service quality strongly influences patient satisfaction, particularly through physical facilities and responsiveness. Hospitals should prioritize improvements in facility readiness, timely service delivery, and patient-centered communication to enhance satisfaction and loyalty. Future studies involving larger and multicenter populations are recommended to strengthen external validity.